Global Pattern of kdr-Type Alleles in Musca domestica (L.) - Roca Acevedo, Gonzalo (2023)
Purpose of Review: Houseflies, Musca domestica L., are an important sanitary pest that affects human and domesticated animals. They are mechanical carriers of more than 100 human and animal diseases including protozoan, bacterial, helminthic, and viral infections. Recently, it was demonstrated that houseflies acquired, harbored, and transmitted SARS-CoV-2 (COVID-19) for up to 1 day post-exposure. The most widely used control strategy relays on the application of pyrethroid insecticides due to their effectiveness, low mammalian toxicity, low cost, and environmental safety. The main mechanism of action of pyrethroids is to exert their toxic effects through affecting the voltage-sensitive sodium channel (VSSC) modifying the transmission of the nerve impulse and leading to the death of the insects. Target site insensitivity of the VSSC is due to the presence of single nuclear polymorphisms (SNPs) named knockdown mutations (kdr). In this review, we synthetize recent data on the type and distribution of these mutations globally. Recent Findings: Housefly resistance is reported in several countries. Increased applications of pyrethroids to control housefly populations led to the emergence of multiple evolutionary origins of resistance determined by five amino acid substitutions or specific mutations in the VSSC: kdr (L1014F), kdr-his (L1014H), super-kdr (M918T + L1014F), type N (D600N + M918T + L1014F), and 1B (T929I + L1014F). According to the global map obtained, high levels of resistance to pyrethroids are associated with the L1014F mutation found mostly in North America, Europe, and Asia, while the super-kdr mutation was mostly found in the American continent. The level of protection conferred by these alleles against pyrethroids was generally kdr-his < kdr < Type N ≤ super-kdr ≤ 1B. The relative fitness of the alleles under laboratory conditions was susceptible ≅ kdr-his > kdr > super-kdr suggesting that the fitness cost of an allele was relative to the presence of other alleles in a population and that the reversion of resistance in a free insecticide environment might be quite variable from one region to another. Summary: An adequate integrated pest management program should consider monitoring susceptibility to pyrethroids to detect early levels of resistance and predict the spread and evolution of resistant phenotypes and genotypes. From this review, the pyrethroid resistance status of housefly population was determined in very few countries and has evolved independently in different areas of the world affecting chemical control programs.